2020
DOI: 10.1001/jamainternmed.2020.1321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Workplace Wellness Program on Employee Health, Health Beliefs, and Medical Use

Abstract: IMPORTANCE Many employers use workplace wellness programs to improve employee health and reduce medical costs, but randomized evaluations of their efficacy are rare.OBJECTIVE To evaluate the effect of a comprehensive workplace wellness program on employee health, health beliefs, and medical use after 12 and 24 months. DESIGN, SETTING, AND PARTICIPANTSThis randomized clinical trial of 4834 employees of the University of Illinois at Urbana-Champaign was conducted from August 9, 2016, to April 26, 2018. Members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 27 publications
1
48
1
5
Order By: Relevance
“…"This randomized clinical trial showed that a comprehensive workplace wellness program had no significant effects on measured physical health outcomes, rates of medical diagnoses, or the use of health care services after 24 months …" [1] Die Ursache dieser Diskrepanz zwischen Bedeutung und Evidenz liegt sehr häufig darin, dass in der Regel [2]: ▪ insgesamt zu wenig Mitarbeiter erreicht werden, ▪ nicht die Mitarbeiter erreicht werden, die den höchsten…”
Section: Betriebliche Gesundheitsförderung Und Evidenzunclassified
“…"This randomized clinical trial showed that a comprehensive workplace wellness program had no significant effects on measured physical health outcomes, rates of medical diagnoses, or the use of health care services after 24 months …" [1] Die Ursache dieser Diskrepanz zwischen Bedeutung und Evidenz liegt sehr häufig darin, dass in der Regel [2]: ▪ insgesamt zu wenig Mitarbeiter erreicht werden, ▪ nicht die Mitarbeiter erreicht werden, die den höchsten…”
Section: Betriebliche Gesundheitsförderung Und Evidenzunclassified
“…Reviews have emerged concluding how WHP appears to be effective in its objectives to improve health, and may also generate a financial return on investment [ 11 , 12 , 13 , 14 ]. However, there are also studies which have cast doubt on conclusions that WHP programs are effective or cost-effective [ 15 , 16 , 17 , 18 ]. Regardless of a scientific effectiveness debate, employers’ interest towards positive impacts on health, productivity, and return-on-investment has generated a demand for potential WHP solutions [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have emerged concluding WHP appears to be effective in its objectives to improve health and may also generate a nancial return on investment [11][12][13][14]. However, there are also studies which have cast doubt on conclusions that WHP programs are effective or costeffective [15,16,17,18]. Regardless of a scienti c effectiveness debate, employers´ interest towards positive impact on health, productivity and return-on-investment has generated a demand for potential WHP solutions [14,19].…”
Section: Introductionmentioning
confidence: 99%